?EQUILIBRIA AND STRUCTURES OF SOME BARBITURATE COMPOUNDS - MASOUD, MAMDOUH S.; NAHAS, HIND M. EL-; HAG GAG, SAWSAN S. (Biological Sciences - PJSIR, 1995)
Some azobarbiturate andbenzylidenebarbituratecompoundswereprepared.The structuralchemistry wasinves- tigated based on different spectral and pH-metric methods. The tautomeric equilibria were explained. The electronic character of the substituents affects the mode of dissociation of the organic compounds.